The Core Contradictions Elements in the Mob of Papua: A Dialectical Ecolinguistics Analysis - Maryanti E. Mokoagouw; Aron Meko Mbete; Ida Bagus Putra Yadnya; Made Sri Satyawati (e-Journal of Linguistics, 2019)
Quite a lot of approaches have been utilized to study humor texts; yet, none has beenfrom an ecolinguistics’ perspective. This article specifically intends to scrutinize a particularhumor text from Papua called mob on the ground of dialectical ecolinguistics as developed byBang, Door, et al. (1993). The main purpose of this article is to describe the elements of corecontradictions (i.e. race, age, sex, class, authority, ideology, town-country, private-public, andculture-nature) found in mob. The result of the analysis shows that all the nine elements of thecore contradictions in mob are found in the bio-logics dimension indicating that the bio-logicsdimension is the most dominant dimension in the world of the mob owners (i.e. the people ofPapua).